2020
DOI: 10.1177/0265407519899704
|View full text |Cite
|
Sign up to set email alerts
|

Convoys of perceived support from adolescence to midlife

Abstract: Data from 963 Canadians at ages 18 (late adolescence), 25 (young adulthood), and 43 (midlife) were used to explore convoys of perceived social support from parents, other family, friends, partners, coworkers, and children. Latent profile and latent transition analyses revealed two support profiles at each age, distinguished by amount of family support. Those with high family support had a high likelihood (approximately 80%) of remaining in that profile from one life stage to the next, while those with low fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…A larger sample would not only improve the generalizability of the results obtained but would also allow for insightful additional analyses. For example, a person‐centred analytical approach that simultaneously considers the properties of all relationships in one's social convoy (e.g., Fang et al, 2020) would enable the identification of relationship patterns that serve as risk or protective factors in RYC adolescents' loneliness. Second, the study failed to collect additional information about the RYC youth that could significantly shape the results obtained (e.g., duration of living in the RYC group homes, how many adolescents lived in each of the participating RYC group homes, what were the specific circumstances leading to their placement in the RYC).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A larger sample would not only improve the generalizability of the results obtained but would also allow for insightful additional analyses. For example, a person‐centred analytical approach that simultaneously considers the properties of all relationships in one's social convoy (e.g., Fang et al, 2020) would enable the identification of relationship patterns that serve as risk or protective factors in RYC adolescents' loneliness. Second, the study failed to collect additional information about the RYC youth that could significantly shape the results obtained (e.g., duration of living in the RYC group homes, how many adolescents lived in each of the participating RYC group homes, what were the specific circumstances leading to their placement in the RYC).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, their social relationships are characterized by less frequent contact, less perceived support and lower satisfaction, which was particularly evident in their relationships with parents and extended family members. As social convoys tend to be moderately stable over time (Ciarrochi et al, 2017; Fang et al, 2020), less favourable convoys could represent a risk for long‐term outcomes. On the other hand, previous research has shown that a substantial proportion of individuals change social convoy profiles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the COVID-19 pandemic, social support from family could have potentially alleviated depression symptoms due to the social lockdown condition (Mariani et al, 2020 ). Moreover, it has been shown that a high level of perceived social support from multiple sources is associated with better physical and psychological health (Fang et al, 2020 ). Thus, social support may be of great importance for protecting one from mental health problems, especially in a crisis, such as the prolonged COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%